2020
DOI: 10.1038/s41598-020-72502-9
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde exposure induces regulatory T cell-mediated immunosuppression via calcineurin-NFAT signalling pathway

Abstract: In this study, we investigated the effects of Formaldehyde (FA) exposure on splenic immune responses wherein helper T cells become activated and differentiate into effector T and regulatory T cells. BALB/c mice were exposed to two FA concentrations (1.38 mg/m3 and 5.36 mg/m3) for 4 h/day and 5 days/week for 2 weeks. FA-induced immune responses were examined by the production of cytokines, expression of mRNAs, and distributions of helper T cells and regulatory T cells. Moreover, expression of calcineurin and NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
3
7
0
Order By: Relevance
“…Our results demonstrate that FA exposure suppressed the expression of all helper T cell-related genes in a concentration-dependent manner, while IL-4 expression was significantly decreased at all inhaled concentrations. These findings are consistent with the results of our previous study, which showed the suppression of Th-1, Th-2, and Th-17 cell-related splenic cytokine production and mRNA expression due to FA exposure in a concentration-dependent manner 46 . Furthermore, Wei et al reported that levels of helper T cell-related cytokines were suppressed in FA-exposed C57BL/6 mice 29 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results demonstrate that FA exposure suppressed the expression of all helper T cell-related genes in a concentration-dependent manner, while IL-4 expression was significantly decreased at all inhaled concentrations. These findings are consistent with the results of our previous study, which showed the suppression of Th-1, Th-2, and Th-17 cell-related splenic cytokine production and mRNA expression due to FA exposure in a concentration-dependent manner 46 . Furthermore, Wei et al reported that levels of helper T cell-related cytokines were suppressed in FA-exposed C57BL/6 mice 29 .…”
Section: Discussionsupporting
confidence: 93%
“…No significant differences were observed between the total and differential cell counts of the FA-exposed and control groups. These findings are consistent with those of previous studies showing that exposure to FA does not induce significant differences in the counts of various inflammatory cell types in bronchoalveolar lavage fluid 30 , 46 . However, in the histopathological analysis, infiltration of inflammatory cells and degeneration of the bronchial epithelium were noted to be increased in the 10.48 mg/m 3 FA exposure group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations